THE ADOPTION OF SISU AND EVASION AT THE FEDERAL UNIVERSITY OF UBERLÂNDIA - João Paulo Gomes Barbosa; Lucio Antonio Portilho; Gilberto José Miranda; Marcelo Tavares (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
The main objective of this study was to determine the percentage of the behavior of dropout students in the years before (2006-2010) and after (2011-2014) the adoption of the Brazilian Unified Selection System (SISU) in the Universidade Federal de Uberlândia (UFU). This is a documentary research. The Data about evasion were obtained with the Dean of Graduate (PROGRAD). In the first part of the verification of information it was held the organization of data on dropout students of the UFU in the period analyzed, and treated 15,088 occurrences. Then the data were classified and summarized and after the binomial statistical test was applied. In the results, the Applied Social Sciences, Humanities and Exact Sciences and Earth areas were those with the highest percentages of dropout students. By analyzing the average by areas, the Agricultural Sciences, Biological Sciences, Engineering, Exact Sciences and Earth and Health Sciences areas presents significant increase in the percentage of dropout students after the SISU. While the Humanities, Linguistics, Literature and Arts and Social Sciences areas showed significant reductions in the percentage of dropout students.